Climate Change Induced Disaster, Gender Conflicts, Risks, and Insecurity in Lower-Gweru Community of Zimbabwe: Towards Capacity Building and Resilience in the Face of Social-Ecological Threats - Winniefridah Matsa (Springer, Cham, 2022)
The ability of our planet Earth to sustain humanity is increasingly threatened as a result of climate change. This challenge is severely hitting the poorest and the most vulnerable resulting in changing patterns of interactions between societal and ecological entities. This chapter is premised on the socio-ecological theoretical framework. The research seeks to determine the unequal impact of climate change disasters on men and women in Lower Gweru community and explore the nexus between climate change, gender-conflicts, risks, and insecurities. It also assesses existing response mechanisms to foster resilience as well as capacity building to enable especially women to cope with challenges posed by climate change, risks, and insecurities. The research is a qualitative exploratory study of four villages of Lower Gweru. The sample consists of four village heads, two councilors, twenty household heads, two police officers, and two Community Health Workers, giving a total of 30 participants. The results revealed that climate change has unequal impact on male and females and cause gender-conflicts, risks, and insecurities. In addition, there are no viable response mechanisms or frameworks to foster resilience; therefore, the research recommends the design of a joint, coordinated and viable model for resilience that merges both gender analysis and climate change disaster resilience frameworks.